Are superficial neuromasts proprioceptors underlying fast copulatory behavior? - Martinez-Rivera, Noraida; Serrano-Velez, Jose L.; Torres-Vazquez, Irma I.; Langerhans, R. Brian; Rosa-Molinar, Eduardo (Frontiers in Neural Circuits, 2022)
In male Poeciliid fishes, the modified anal fin (i.e., gonopodium) and its axial and appendicular support are repositioned within the axial skeleton, creating a novel sexually dimorphic ano-urogenital region. During copulation, the relative location of the gonopodium is crucial for successful insemination. Therefore, the repositioning of these structures and organ relied on the reorganization of the efferent circuitry that controls spinal motor neurons innervating appendicular muscles critical for the movement of the gonopodium, including the fast and synchronous torque-trust motion during insemination attempts. Copulation occurs when males position themselves largely outside a female’s field of view, circumducts their gonopodium, and perform a rapid, complex maneuver to properly contact the female urogenital sinus with the distal tip of the gonopodium to transfer sperm. Although understanding of the efferent circuitry has significantly increased in the last twenty-four years, nothing is known about the cutaneous receptors involved in gonopodium movement, nor how the afferent signals are processed to determine the location of this organ during copulation. Using Western mosquitofish, Gambusia affinis, as our model, we attempt to fill this gap in knowledge here. Preliminary data showed cutaneous nerves and sensory neurons innervating superficial neuromasts surrounding the base of adult male gonopodium; those cutaneous nerves projected ventrally from the spinal cord through the 14th dorsal root ganglion and its corresponding ventral root towards the base and fin rays of the gonopodium. Here we asked what role the cutaneous superficial neuromasts play in controlling the positioning and timing of the gonopodium’s fast and synchronous movements for effective sperm transfer. We first found a greater number of superficial neuromasts surrounding the base of the male’s gonopodium compared to the base of the female’s anal fin. Second, we systemically removed superficial neuromasts surrounding the gonopodium base and observed significant impairment of the positioning and timing of gonopodial movements. Our findings provide a first step to supporting the following hypothesis: during radical reorganization of the Poeciliid body plan, superficial neuromasts have been partially co-opted as proprioceptors that allow the gonopodium to control precise positioning and timing during copulatory attempts.